O corpo do terapeuta no atendimento on-line: afetos produzidos na experiência clínica - Costa, Cléa Maria Alonso da (2021)
The present work aims to discuss the therapist's body on the online clinical process and how the affection produced in this field simultaneously crosses the consultant's body, making it more aware and enhancing it for the creation of new possibilities from the relationship that emerges in this encounter. Understanding that the virtual field is not opposed to the real one, but meets the opening of possibilities, the therapist's body is an important instrument in this relationship, as it is the one who must guarantee the necessary support for the consultant's encounter and growth. Thus, being present and engaged in this clinical field says much more about availability and the implication in this relationship than physical presence. Through a case study and guided by qualitative research, this discussion deepens the understanding of how the body is affected on the online care modality, bringing a reflection based on the phenomenology of Maurice Merleau-Ponty and on the foundations of the Gestalt-therapy developed by Perls, Hefferline and Goodman, thinking of a clinic in which alterity and ethics are premises in the search for a de-alienating and empowering clinical practice in which technology optimizes and provides opportunities for the extension of presence. Thinking of the clinic as a place of experience for new ways of being in relation to the other is the same as awakening the client to the interrelationship with the environment, deliberately exploring the potentiality that arises as a creation in the present time of this field. For all these aspects, I understand that there is no single answer, much less a rule to be followed in the face of the encounter that opens up in the clinic, as it is not just the therapist or only the consulent with their demands, bur a unique and totally new that emerges from that encounter